Particle transport after pellet injection in the TJ-II stellarator. (12th July 2016) - Velasco, J L; McCarthy, K J; Panadero, N; Satake, S; López-Bruna, D; Alonso, A; Calvo, I; Dinklage, A; Estrada, T; Fontdecaba, J M; Hernández, J; García, R; et al.
Abstract: We study radial particle transport in stellarator plasmas using cryogenic pellet injection. By means of perturbative experiments, we estimate the experimental particle flux and compare it with neoclassical simulations. Experimental evidence is obtained of the fact that core depletion in helical devices can be slowed-down even by pellets that do not reach the core region. This phenomenon is well captured by neoclassical predictions with DKES and FORTEC-3D.